2020
DOI: 10.1186/s13071-020-04261-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a universal PCR assay to identify different Leishmania species causative of Old World cutaneous leishmaniasis

Abstract: Background: The characterization of Leishmania species is important for clinical management of the diseases and the epidemiological control of the parasite distribution. Most of the published polymerase chain reaction (PCR) amplification methods lack the ability to identify all species complexes, have low performance and usually need post-PCR procedures. There is a need for improving the diagnosis of CL by development of an accurate affordable PCR method to identify all Leishmania species in clinical specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This method can be time consuming, requires an array of equipment and, as the PCR tube containing amplicons must be opened for electrophoresis, is associated with a risk of contamination [ 169 ]. Clinical sensitivity and specificity of up to 100% each have been achieved for lesion samples, with detection of as low as 0.01–0.1 pg of cultured Leishmania promastigote DNA [ 170 ].…”
Section: Methods For the Detection And Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…This method can be time consuming, requires an array of equipment and, as the PCR tube containing amplicons must be opened for electrophoresis, is associated with a risk of contamination [ 169 ]. Clinical sensitivity and specificity of up to 100% each have been achieved for lesion samples, with detection of as low as 0.01–0.1 pg of cultured Leishmania promastigote DNA [ 170 ].…”
Section: Methods For the Detection And Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…Based on PCR analysis, 28 of 41 (68.3%) lesional samples were characterized as L. major and the remaining 13 isolates (31.7%) were identified as L. tropica. The identity of the strains was confirmed with molecular methods (Nateghi Rostami et al, 2020).…”
Section: 1demographic and Clinical Resultsmentioning
confidence: 95%
“…The DNAs were kept at -20 °C until further use. Species identification of the isolates was performed by species specific primers with multiplex PCR method targeting kinetoplast DNA and a nested-PCR restriction fragment length polymorphism (RFLP) targeting internal transcribed spacer 2 (ITS2) region as previously described (Nateghi Rostami et al, 2020).…”
Section: 2dna Extraction and Leishmania Species Identificationmentioning
confidence: 99%
“…Moreover, a pan- Leishmania assay can also be exploited in eco-epidemiological studies, including identification of vectors and reservoirs [ 24 ]. In recent years, only a few attempts to develop pan- Leishmania assays based on nucleic acids amplification (i.e., SL RNA, rDNA or kDNA minicircles) have been made [ 24 , 25 , 26 , 27 ]. We previously showed that qPCR-ML was able to detect Old World L. ( L .)…”
Section: Discussionmentioning
confidence: 99%